Self-lubricating high-wear-resistance coating and preparation method thereof
By converting TiO2 into a rutile type and introducing fibers and MAX phases, combined with pre-oxidation to generate metal oxide films, the coating brittleness and wear problems in polysilicon equipment are solved, and high wear resistance, self-lubricating and high toughness coatings are achieved, extending the equipment's service cycle and improving product purity.
Patent Information
- Application Number
- CN202510032518.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-09
AI Technical Summary
In polysilicon silicon powder conveying equipment and pipelines, metal parts are scrapped due to wear, and the metal generated by wear causes the impurity content of polysilicon products to increase. The existing ceramic coatings are prone to increase brittleness and fail quickly during the silicon powder erosion process.
By converting all anatase-type TiO2 into rutile-type TiO2 and introducing fibers and MAX phases into the coating, the thin layer of TiO2 bridges the fibers and plasma spray particles using capillary force and surface tension to increase the toughness of the coating, and a stable metal oxide film is generated by pre-oxidation to lubricate the wear.
It improves the high temperature stability, wear resistance and fracture toughness of the coating, reduces the damage to the coating by particle erosion and wear, extends the service life of the equipment and improves the purity of polysilicon products.
Smart Images

Figure CN119843200A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polysilicon coating protection, and relates to a self-lubricating high-wear-resistant coating and a preparation method thereof. Background Art
[0002] In polysilicon powder conveying equipment and pipelines, metal parts will wear out and become scrapped after a period of use, and the metal produced by wear can easily increase the impurity content of polysilicon products. At present, surface treatment technology is often used, and surface wear can be effectively improved by applying a layer of coating on the substrate. Atmospheric plasma sprayed titanium oxide ceramic coating has the advantages of high strength, high hardness, high wear resistance, and stable chemical properties. It is suitable for use as a wear-resistant coating in the field of polysilicon production, which can greatly increase the service life of the equipment. However, during the process of silicon powder washing the coating, the frictional heat generated by friction will cause the coating pores to sinter and the grains to grow, resulting in increased brittleness of the coating and rapid failure.
[0003] Therefore, it is necessary to provide a self-lubricating high wear-resistant coating and a preparation method thereof to improve the fracture toughness and lubricity of the ceramic coating, reduce the expansion of cracks in the coating during service, and reduce the damage to the coating caused by the synergistic effect of particle erosion and wear. Summary of the invention
[0004] In order to overcome the problems in the background technology, the present invention improves the high-temperature stability and wear resistance of the coating by completely converting the anatase TiO2 into rutile TiO2, and utilizes the capillary force and surface tension at the fiber interface to which nano-TiO2 adheres, so that the thin TiO2 layer is beneficial to the bridging between the fiber and the plasma sprayed particles, thereby increasing the toughness of the coating. At the same time, a stable metal oxide film (TiO2, Al2O3) is generated on the surface of the coating through pre-oxidation, which has a lubricating effect on wear.
[0005] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0006] In one aspect, the present invention provides a method for preparing a self-lubricating high wear-resistant coating, the preparation method comprising the following steps:
[0007] (1) TiO2 powder, MAX phase and fiber are wet ball-milled to obtain composite powder, wherein the mass fraction of MAX phase is 10-15%, the mass fraction of fiber is 2-5%, and the balance is TiO2, wherein the MAX phase comprises one of Ti2AlC, Ti3SiC2 and Cr2AlC. The particle size of titanium oxide is less than 100 nm, and the aspect ratio of fiber is greater than 100.
[0008] (2) Add the composite powder obtained in step (1) into water, add polyvinyl alcohol, a dispersant, and a defoamer into the water, and continue ball milling to obtain a slurry. Deionized water is preferably used.
[0009] (3) Using the slurry obtained in the step (2) to perform spray powdering to obtain composite agglomerated powder.
[0010] (4) chemically plating nickel on the composite agglomerated powder obtained in step (3) to obtain nickel-coated powder.
[0011] (5) The nickel-coated powder obtained in step (4) is treated by a plasma spheroidization method to obtain a spraying raw material.
[0012] (6) Using supersonic plasma spraying, spray the coating material in step (5) onto the surface of the component.
[0013] (7) performing isothermal pre-oxidation heat treatment on the coating sprayed in step (6).
[0014] Preferably, in step (1), the fiber comprises one of SiC, C, and Al2O3.
[0015] Preferably, in step (1), the ball-to-material ratio is 3:1, the ball milling speed is 500 r / min, and the ball milling time is 2 h.
[0016] Preferably, in step (2), the dispersant is polyethylene glycol, the defoaming agent is tributyl phosphate, and after the composite powder is added to water, the solid content in the liquid is 40%, the mass of the polyvinyl alcohol added is 3% of the total mass of the liquid, the amount of the dispersant added is 0.1% of the total mass of the liquid, the amount of the defoaming agent added is 0.1% of the total mass of the liquid, and the ball milling time is 2 hours.
[0017] Preferably, in step (3), the spray powdering air inlet temperature is 235-255°C, the air outlet temperature is 95-105°C, the pressure in the tower is 0.05 kPa, the peristaltic pump opening is 26%, and the atomizer speed is 25000 RPM.
[0018] Preferably, in step (4), the specific method of chemical nickel plating is: first, add 3-3.2% NiSiO4·6H2O by weight of water, 3-3.3% Na3C6H5O7·6H2O by weight of water, 3.5-3.8% NaHPO2·H2O by weight of water and 3.5-4% HBO3 by weight of water into water to prepare a nickel plating solution; then add HNO3 into the nickel plating solution to adjust the pH of the nickel plating solution to pH=9; thereafter, heat the nickel plating solution to 50-60°C, and under stirring, add 10-15% of the total mass of the composite agglomerated powder into the nickel plating solution, after nickel plating for 30-60 minutes, filter the nickel plating solution to obtain powder, and then dry the powder to obtain nickel-coated powder.
[0019] Preferably, in the step (5), the powder feeding rate is 15-20 g / min, the system pressure is 50-82.68 kPa, the power is 30-35 kW, the carrier gas is N2, the carrier gas flow rate is 3 L / min, the central gas is a mixed gas of Ar and H2, wherein the volume of H2 accounts for 30% of the total volume of the mixed gas, the mixed gas flow rate is 35-45 L / min, and the powder particle size in the coating raw material obtained after plasma spheroidization is 15-45 μm.
[0020] Preferably, in the step (6), the supersonic plasma spraying power is 58 kW, the spraying voltage is 130 V, the spraying current is 500 A, the Ar gas flow rate is 220 L / min, the H2 flow rate is 11 L / min, the powder feeding rate is 15 g / min, the spray gun moving speed is 300 mm / s, the spraying angle is 90°, the deposition number is 5 times, and the spraying distance is 120 mm.
[0021] Preferably, in step (7), the specific process of the isothermal pre-oxidation heat treatment is: in a heat treatment muffle furnace, the coating is heated to 1200-1300° C., kept warm for 10-15 hours, and then the coating is allowed to cool naturally to room temperature.
[0022] Another aspect of the present invention provides a self-lubricating and highly wear-resistant coating, which is prepared by the above-mentioned preparation method.
[0023] Beneficial effects of the present invention:
[0024] 1. In the fiber-doped coating, anatase TiO2 is completely transformed into rutile TiO2. Rutile TiO2 has better high temperature stability and wear resistance.
[0025] 2. The fibers form a network skeleton structure in the coating, and capillary force and surface tension occur at the fiber interface where nano-TiO2 adheres. The thin TiO2 layer is conducive to the bridging between the fibers and the plasma sprayed particles, thereby increasing the toughness of the coating.
[0026] 3. Composite powders prepared by spray drying of nanopowders, with uniform distribution of fiber and MAX phases.
[0027] 4. The Ni-coated powder is treated by plasma spheroidization. The molten softer metal Ni particles can fill the gaps between particles, improve the sphericity and density of the powder, and ensure the integrity of the powder during spraying.
[0028] 5. The coating is subjected to isothermal pre-oxidation heat treatment to dissolve the grain boundaries in the coating structure, grow rapidly, and rearrange the atoms in the lattice. The original pores will become smaller or filled. On the one hand, the porosity of the coating can be reduced. On the other hand, the stable metal oxide film (TiO2, Al2O3) generated on the coating surface can lubricate the wear.
[0029] 6. During the wear process of silicon particles, wear-resistant phases such as Ti3SiC2, SiO2, SiO2-Al2O3, SiC, and TiAl can be generated in situ, further improving the wear resistance of the coating.
[0030] 7. The coating porosity after spraying of the present invention is ≤0.1%, the friction coefficient is ≤0.25, and the hardness is ≥500HV 0.3 , wear rate ≤2×10 -17 m 3 / (N·m). BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a microscopic morphology of the coating prepared in Example 1 of the present invention, wherein Figure (b) is a partial enlarged view of Figure (a). DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the described contents.
[0033] In the examples and comparative examples of the present invention, chemical reagents not otherwise specified were all commercially available analytically pure reagents for the experiments.
[0034] The coating compositions of the embodiments of the present invention and the comparative examples are shown in Table 1.
[0035] Table 1
[0036]
[0037] Example 1
[0038] This example prepares the coating as follows:
[0039] (1) Weigh TiO2 nano-ceramic powder with a particle size less than 100 nm, MAX phase, and SiC fiber with an aspect ratio greater than 100 according to the mass fractions in Table 1. The total mass of the coating raw materials is determined according to conventional specifications.
[0040] (2) First, TiO2 nano-ceramic powder, Max phase, and fiber are placed in a planetary ball mill and wet-milled for 2 h at a ball-to-material ratio of 3:1 and a rotation speed of 500 r / min to obtain a composite powder, so that the powders are mixed evenly. Wet milling can avoid destroying the layered structure of the MAX phase and the rod-like structure of the fiber compared to dry milling.
[0041] (3) The composite powder is made into a slurry with deionized water. After the composite powder is added to the water, the solid content in the liquid is 40%. Then, 3% of the total mass of the liquid is polyvinyl alcohol (PVA), 0.1% of the total mass of the liquid is a dispersant (PEG), and 0.1% of the total mass of the liquid is a defoaming agent (tributyl phosphate). The ball milling is continued for 2 hours.
[0042] (4) A centrifugal spray dryer was used to spray powder at an inlet air temperature of 245° C., an outlet air temperature of 100° C., an inner tower pressure of 0.05 kPa, a peristaltic pump opening of 26%, and an atomizer speed of 25000 RPM to obtain a composite agglomerated powder.
[0043] (5) Coating the agglomerated powder with a chemical nickel plating process to obtain a nickel-coated powder. First, take deionized water, add NiSiO4·6H2O, Na3C6H5O7·6H2O, NaHPO2·H2O, and HBO3 to the deionized water, wherein NiSiO4·6H2O is 3.1% of the weight of the deionized water, Na3C6H5O7·6H2O is 3.2% of the weight of the deionized water, NaHPO2·H2O is 3.6% of the weight of the deionized water, and HBO3 is 3.8% of the weight of the deionized water to prepare a nickel plating solution; secondly, adjust the pH value of the solution with HNO3 to make pH = 9; then, adjust the magnetic stirrer, add 12% of the total mass of the composite agglomerated powder of the nickel plating solution at a temperature of 55°C, and stir for 45 minutes. Finally, filter out the powder with a filter funnel and dry it to obtain a nickel-coated powder.
[0044] (6) The nickel-coated powder is densified by plasma spheroidization. In the control system, the system pressure, central gas flow rate, power are set, the system is started, and powder feeding begins. The powder feeding rate is 18 g / min, the system pressure is 60 kPa, the power is 32 kW, the carrier gas is N2, the carrier gas flow rate is 3 L / min, the central gas is Ar+30 vol.% H2, and the flow rate is 40 L / min. The obtained powder particle size is 15 to 45 microns, which is used as a spraying raw material.
[0045] (7) Spray coating. Use supersonic plasma spraying technology to spray the spraying raw materials onto the surface of the workpiece. During the spraying process, the spraying power is 58kW, the spraying voltage is 130V, the spraying current is 500A, the Ar gas flow rate is 220L / min, the H2 flow rate is 11L / min, the powder feeding rate is 15g / min, the spray gun moving speed is 300mm / s, the spraying angle is 90°, the deposition number is 5 times, and the spraying distance is 120mm.
[0046] (8) Isothermal pre-oxidation heat treatment of the coating: The sprayed coating is heated to 1250°C in a muffle furnace and kept at this temperature for 13 hours, then the power of the heating furnace is turned off and the coating is allowed to cool naturally to room temperature.
[0047] The microstructure of the coating prepared in this embodiment is as follows: Figure 1 As shown, through Figure 1 It can be seen that the powder and whiskers are tightly combined, the whiskers are evenly distributed in the coating, and the whiskers are wrapped by powder particles. This thin layer is conducive to the bridging of whiskers between plasma sprayed particles, which can effectively transfer and disperse stress and prevent the expansion of cracks, thereby improving the overall strength and toughness of the coating.
[0048] The friction coefficient and fracture toughness of the coating prepared in this example were measured, and the results are shown in Table 2.
[0049] Example 2
[0050] This example prepares the coating as follows:
[0051] (1) Weigh TiO2 nano-ceramic powder with a particle size less than 100 nm, MAX phase, and C fibers with an aspect ratio greater than 100 according to the mass fractions in Table 1. The total mass of the coating raw materials is determined according to conventional specifications.
[0052] (2) First, TiO2 nano-ceramic powder, Max phase, and fiber are placed in a planetary ball mill and wet-milled for 2 h at a ball-to-material ratio of 3:1 and a rotation speed of 500 r / min to obtain a composite powder, so that the powders are mixed evenly. Wet milling can avoid destroying the layered structure of the MAX phase and the rod-like structure of the fiber compared to dry milling.
[0053] (3) The composite powder is made into a slurry with deionized water. After the composite powder is added to the water, the solid content in the liquid is 40%. Then, 3% of the total mass of the liquid is polyvinyl alcohol (PVA), 0.1% of the total mass of the liquid is a dispersant (PEG), and 0.1% of the total mass of the liquid is a defoaming agent (tributyl phosphate). The ball milling is continued for 2 hours.
[0054] (4) A centrifugal spray dryer was used to spray powder at an inlet air temperature of 235° C., an outlet air temperature of 95° C., an inner tower pressure of 0.05 kPa, a peristaltic pump opening of 26%, and an atomizer speed of 25000 RPM to obtain a composite agglomerated powder.
[0055] (5) Coating the agglomerated powder with a chemical nickel plating process to obtain a nickel-coated powder. First, take deionized water, add NiSiO4·6H2O, Na3C6H5O7·6H2O, NaHPO2·H2O, and HBO3 to the deionized water, wherein NiSiO4·6H2O is 3% of the weight of the deionized water, Na3C6H5O7·6H2O is 3% of the weight of the deionized water, NaHPO2·H2O is 3.5% of the weight of the deionized water, and HBO3 is 3.5% of the weight of the deionized water to prepare a nickel plating solution; secondly, adjust the pH value of the solution with HNO3 to make pH = 9; then, adjust the magnetic stirrer, add 15% of the total mass of the composite agglomerated powder of the nickel plating solution at a temperature of 50°C, and stir for 60 minutes. Finally, filter out the powder with a filter funnel and dry it to obtain a nickel-coated powder.
[0056] (6) The nickel-coated powder is densified by plasma spheroidization. In the control system, the system pressure, central gas flow rate, power are set, the system is started, and powder feeding begins. The powder feeding rate is 15 g / min, the system pressure is 50 kPa, the power is 30 kW, the carrier gas is N2, the carrier gas flow rate is 3 L / min, the central gas is Ar+30 vol.% H2, and the flow rate is 35 L / min. The obtained powder particle size is 15 to 45 microns, which is used as a spraying raw material.
[0057] (7) Spray coating. Use supersonic plasma spraying technology to spray the spraying raw materials onto the surface of the workpiece. During the spraying process, the spraying power is 58kW, the spraying voltage is 130V, the spraying current is 500A, the Ar gas flow rate is 220L / min, the H2 flow rate is 11L / min, the powder feeding rate is 15g / min, the spray gun moving speed is 300mm / s, the spraying angle is 90°, the deposition number is 5 times, and the spraying distance is 120mm.
[0058] (8) Isothermal pre-oxidation heat treatment of the coating: The sprayed coating is heated to 1200°C in an argon atmosphere and kept at this temperature for 15 hours, then the power of the heating furnace is turned off and the coating is allowed to cool naturally to room temperature.
[0059] The coating performance prepared in this example is similar to that in Example 1.
[0060] Example 3
[0061] This example prepares the coating as follows:
[0062] (1) Weigh TiO2 nano-ceramic powder with a particle size less than 100 nm, MAX phase, and Al2O3 fiber with an aspect ratio greater than 100 according to the mass fractions in Table 1. The total mass of the coating raw materials is determined according to conventional specifications.
[0063] (2) First, TiO2 nano-ceramic powder, Max phase, and fiber are placed in a planetary ball mill and wet-milled for 2 h at a ball-to-material ratio of 3:1 and a rotation speed of 500 r / min to obtain a composite powder, so that the powders are mixed evenly. Wet milling can avoid destroying the layered structure of the MAX phase and the rod-like structure of the fiber compared to dry milling.
[0064] (3) The composite powder is made into a slurry with deionized water. After the composite powder is added to the water, the solid content in the liquid is 40%. Then, 3% of the total mass of the liquid is polyvinyl alcohol (PVA), 0.1% of the total mass of the liquid is a dispersant (PEG), and 0.1% of the total mass of the liquid is a defoaming agent (tributyl phosphate). The ball milling is continued for 2 hours.
[0065] (4) A centrifugal spray dryer was used to spray powder at an inlet air temperature of 255° C., an outlet air temperature of 105° C., an inner tower pressure of 0.05 kPa, a peristaltic pump opening of 26%, and an atomizer speed of 25000 RPM to obtain a composite agglomerated powder.
[0066] (5) Coating the agglomerated powder with a chemical nickel plating process to obtain a nickel-coated powder. First, take deionized water, add NiSiO4·6H2O, Na3C6H5O7·6H2O, NaHPO2·H2O, and HBO3 to the deionized water, wherein NiSiO4·6H2O is 3.2% of the weight of the deionized water, Na3C6H5O7·6H2O is 3.3% of the weight of the deionized water, NaHPO2·H2O is 3.8% of the weight of the deionized water, and HBO3 is 4% of the weight of the deionized water to prepare a nickel plating solution; secondly, adjust the pH value of the solution with HNO3 to make pH = 9; then, adjust the magnetic stirrer, add 10% of the total mass of the composite agglomerated powder of the nickel plating solution at a temperature of 60°C, and stir for 30 minutes. Finally, filter out the powder with a filter funnel and dry it to obtain a nickel-coated powder.
[0067] (6) The nickel-coated powder is densified by plasma spheroidization. In the control system, the system pressure, central gas flow rate, power are set, the system is started, and powder feeding begins. The powder feeding rate is 20 g / min, the system pressure is 82.68 kPa, the power is 35 kW, the carrier gas is N2, the carrier gas flow rate is 3 L / min, the central gas is Ar+30 vol.% H2, and the flow rate is 45 L / min. The obtained powder particle size is 15 to 45 microns, which is used as a spraying raw material.
[0068] (7) Spray coating. Use supersonic plasma spraying technology to spray the spraying raw materials onto the surface of the workpiece. During the spraying process, the spraying power is 58kW, the spraying voltage is 130V, the spraying current is 500A, the Ar gas flow rate is 220L / min, the H2 flow rate is 11L / min, the powder feeding rate is 15g / min, the spray gun moving speed is 300mm / s, the spraying angle is 90°, the deposition number is 5 times, and the spraying distance is 120mm.
[0069] (8) Isothermal pre-oxidation heat treatment of the coating: The sprayed coating is heated to 1300°C in an argon atmosphere and kept at this temperature for 10 hours, then the power of the heating furnace is turned off and the coating is allowed to cool naturally to room temperature.
[0070] The coating performance prepared in this example is similar to that in Example 1.
[0071] Comparative Example 1
[0072] The coating in this comparative example is prepared by the same method as in Example 1, except that the coating in this comparative example does not contain MAX phase and fiber (as shown in Table 1).
[0073] The friction coefficient and fracture toughness of the coating prepared in this comparative example were measured, and the results are shown in Table 2.
[0074] Comparative Example 2
[0075] The coating in this comparative example was prepared by the same method as in Example 1, except that the coating in this comparative example did not contain a MAX phase (as shown in Table 1).
[0076] The friction coefficient and fracture toughness of the coating prepared in this comparative example were measured, and the results are shown in Table 2.
[0077] Comparative Example 3
[0078] The coating in this comparative example was prepared by the same method as in Example 1, except that the coating in this comparative example did not contain fibers (as shown in Table 1).
[0079] The friction coefficient and fracture toughness of the coating prepared in this comparative example were measured, and the results are shown in Table 2.
[0080] Table 2
[0081] Friction coefficient <![CDATA[Fracture toughness / MPa·m 1 / 2 > Example 1 0.32 4.47 Comparative Example 1 0.56 1.25 Comparative Example 2 0.51 4.58 Comparative Example 3 0.34 1.38
[0082] From the comparison in Table 2, it can be seen that the MAX phase plays a major role in self-lubrication: The self-lubrication principle of MAX phase materials is that under the influence of friction and thermal forces, the M-position (metal) and A-position (aluminum or metalloid) elements will diffuse to the surface of the material and combine with oxygen in the environment to continuously generate a stable oxide lubricating film. This lubricating film can effectively reduce the friction coefficient and wear rate of the material.
[0083] It can also be seen from the comparison in Table 2 that the addition of fibers is beneficial to the toughening of the coating. The principle of fiber toughening is:
[0084] (1) Crack deflection: When the bonding force between the fiber and the coating molten particles is weak, the crack will deviate from the original path during the propagation process and propagate along the bonding surface between the fiber and the coating molten particles, causing debonding at the fiber-coating molten particle interface, thereby hindering crack propagation.
[0085] (2) Fiber pull-out: During the crack propagation process, the fiber will be debonded and pulled out from the coating molten particles. The fiber pull-out will relax the stress at the crack tip, slow down the crack propagation, and consume the energy of crack propagation.
[0086] (3) Bridge Effect: When the fibers in the coating are bridged, their two ends will pull the two crack surfaces, that is, compressive stress will be generated on the crack surface, offsetting part of the effect of the external pressure and preventing the crack from further expanding.
[0087] In summary, the coating of the present invention has excellent wear resistance, self-lubricating properties and fracture toughness, and can provide long-term protection for polysilicon powder conveying equipment and pipelines, thereby further improving the purity of polysilicon products and extending the service life of the equipment.
[0088] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A method for preparing a self-lubricating and highly wear-resistant coating, characterized in that: The preparation method comprises the following steps: (1) Wet ball milling TiO2 powder, MAX phase and fiber to obtain composite powder, wherein the composite powder has a MAX phase mass fraction of 10-15%, a fiber mass fraction of 2-5%, and the remainder is TiO2, and the MAX phase includes one of Ti2AlC, Ti3SiC2 and Cr2AlC; (2) adding the composite powder obtained in step (1) into water, adding polyvinyl alcohol, a dispersant, and a defoaming agent into the water, and continuing ball milling to obtain a slurry; (3) using the slurry obtained in step (2) to perform spray powdering to obtain a composite agglomerated powder; (4) chemically plating nickel on the composite agglomerated powder obtained in step (3) to obtain a nickel-coated powder; (5) treating the nickel-coated powder obtained in step (4) by a plasma spheroidization method to obtain a spraying raw material; (6) using supersonic plasma spraying to spray the coating material in step (5) onto the surface of the component; (7) performing isothermal pre-oxidation heat treatment on the coating sprayed in step (6).
2. The preparation method according to claim 1, characterized in that: In the step (1), the fiber includes one of SiC, C, and Al2O3.
3. The preparation method according to claim 1, characterized in that: In the step (1), the ball-to-material ratio is 3:1, the ball milling speed is 500 r / min, and the ball milling time is 2 h.
4. The preparation method according to claim 1, characterized in that: In the step (2), the dispersant is polyethylene glycol, the defoaming agent is tributyl phosphate, and after the composite powder is added to water, the solid content in the liquid is 40%, the added mass of polyvinyl alcohol is 3% of the total mass of the liquid, the added amount of the dispersant is 0.1% of the total mass of the liquid, the added amount of the defoaming agent is 0.1% of the total mass of the liquid, and the ball milling time is 2 hours.
5. The preparation method according to claim 1, characterized in that: In the step (3), the inlet air temperature of the spray powder making is 235-255°C, the outlet air temperature is 95-105°C, the pressure in the tower is 0.05 kPa, the peristaltic pump opening is 26%, and the atomizer speed is 25000 RPM.
6. The preparation method according to claim 1, characterized in that: In the step (4), the specific method of chemical nickel plating is: first, add 3-3.2% of NiSiO4·6H2O by weight of water, 3-3.3% of Na3C6H5O7·6H2O by weight of water, 3.5-3.8% of NaHPO2·H2O by weight of water, and 3.5-4% of HBO3 by weight of water into water to prepare a nickel plating solution; then add HNO3 to the nickel plating solution to adjust the pH of the nickel plating solution to pH=9; Afterwards, the nickel plating solution is heated to 50-60° C., and under stirring, 10-15% of the total mass of the composite agglomerated powder is added to the nickel plating solution. After nickel plating for 30-60 minutes, the nickel plating solution is filtered to obtain powder, and then the powder is dried to obtain nickel-coated powder.
7. The preparation method according to claim 1, characterized in that: In the step (5), the powder feeding rate is 15-20 g / min, the system pressure is 50-82.68 kPa, the power is 30-35 kW, the carrier gas is N2, the carrier gas flow rate is 3 L / min, the central gas is a mixed gas of Ar and H2, wherein the volume of H2 accounts for 30% of the total volume of the mixed gas, the mixed gas flow rate is 35-45 L / min, and the powder particle size in the coating raw material obtained after plasma spheroidization is 15-45 μm.
8. The preparation method according to claim 1, characterized in that: In the step (6), the supersonic plasma spraying power is 58 kW, the spraying voltage is 130 V, the spraying current is 500 A, the Ar gas flow rate is 220 L / min, the H2 flow rate is 11 L / min, the powder feeding rate is 15 g / min, the spray gun moving speed is 300 mm / s, the spraying angle is 90°, the deposition number is 5 times, and the spraying distance is 120 mm.
9. The preparation method according to claim 1, characterized in that: In the step (7), the specific process of the isothermal pre-oxidation heat treatment is: heating the coating to 1200-1300° C., keeping the temperature for 10-15 hours, and then allowing the coating to cool naturally to room temperature.
10. The self-lubricating and highly wear-resistant coating prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Short fiber-particle synergetically-reinforced copper-based composite material and preparation method thereof
CN102978434A
Preparation method of TiO2-SiC-fiber filled polytetrafluoroethylene composite material
CN103333442A
Coating inorganic fiber toughened MAX phase ceramic composite material, preparation method and uses thereof
CN103910532A
Preparation method of Al2O3 fiber-toughened MAX-phase ceramic matrix composite
CN104628407A
High-temperature abrasion resistant composite material and preparation method thereof
CN107747070A
Cited By
Self-lubricating anti-attrition coating as well as preparation method and application thereof
CN120082837A